Altered cortical development in fetuses with isolated nonsevere ventriculomegaly assessed by neurosonography. (19th April 2018) - Hahner, Nadine; Puerto, Bienvenido; Perez‐Cruz, Miriam; Policiano, Catarina; Monterde, Elena; Crispi, Fatima; Gratacos, Eduard; Eixarch, Elisenda
Abstract: Objectives: To perform a comprehensive assessment of cortical development in fetuses with isolated nonsevere ventriculomegaly (INSVM) by neurosonography. Methods: We prospectively included 40 fetuses with INSVM and 40 controls. INSVM was defined as atrial width between 10.0 and 14.9 mm without associated malformation, infection, or chromosomal abnormality. Cortical development was assessed by neurosonography at 26 and 30 weeks of gestation measuring depth of selected sulci and applying a maturation scale from 0 (no appearance) to 5 (maximally developed) of main sulci and areas. Results: INSVM showed underdeveloped calcarine and parieto‐occipital sulci. In addition, significant delayed maturation pattern was also observed in regions distant to ventricular system including Insula depth (controls 30.8 mm [SD 1.7] vs INSVM 31.7 mm [1.8]; P =  .04), Sylvian fissure grading (>2 at 26 weeks: controls 87.5% vs INSVM 50%, P  = .01), mesial area grading (>2 at 30 weeks: controls 95% vs INSVM 62.5%; P  = .03), and cingulate sulcus grading (>2 at 30 weeks: controls 100% vs INSVM 80.5%; P  = .01). Conclusions: Fetuses with INSVM showed underdeveloped cortical maturation including also regions, where effect of ventricular dilatation is unlikely. These results suggest that in a proportion of fetuses with INSVM, ventricular dilation might be related with altered cortical architecture. Abstract : What's already known about this topic? Fetuses with isolated nonsevere ventriculomegaly are at risk of neurodevelopmental impairment. Calcarine and parieto‐occipital fissure have been demonstrated to present differential development in ventriculomegaly. What does the study add? This study provides a comprehensive evaluation of cortical development in isolated nonsevere ventriculomegaly including regions that have not been explored previously. This study demonstrates that fetuses with isolated nonsevere ventriculomegaly have underdeveloped cortical maturation, also in regions that are unlikely to be affected by mechanical effect due to ventricular dilation, including Sylvian fissure, mesial area, and cingulate sulcus.